RESIDUAL STRESS ANALYSIS OF UNCOOLED INFRARED FOCAL PLANE ARRAYS BY MICRO-RAMAN SPECTROSCOPY - CEN Hao; WANG KeYong (Jixie qiangdu)
The uncooled infrared focal plane arrays（ UIRFPA） used in this micro-Raman experiment are composed of Si O2 thin film and Si substrate. They have the characteristic of MEMS microstructure. The process of the thermal oxidation may lead to the residual stress on account of thermal ecpansion coefficient mismatch and lattice mismatch. Residual stress in thin film has an important effect on the properties of the micro-elements. Therefore,it is necessary to measure the film residual stress. The residual stress in two Si O2 thin film / Si substrate has been investigated by using micro-Raman spectroscopy（ MRS）. The results show that the residual stress along the cross – section of the Si substrate is a quadric decrease along with an increase in the depth. By means of the force equilibrium and infinitesimal calculus,the residual stress in thin flim can reach 3. 3GPa and2. 2GPa respectively for two samples. Then it can be concluded that residual stress in thin flim is compressive considered the analysis of flim micro-element. In the releasing process of the residual stress,it may make film fold,bend,bulge,and even cause disorder for the film sample when the residual stress reaches GPa level.